Assessing effects of pairing between stimuli via software to promote attention to voices in children diagnosed with Autism Spectrum Disorder (Research, Society and Development, 2020)
Children diagnosed with Autistic Spectrum Disorder (ASD) commonly have difficulties when performing activities that involve auditory discrimination. The skills that are required for such repertoire can be evaluated with some tests, among which ABLA-R stands out. The purpose of the present study was to explore the effectiveness of an application developed for the study in increasing exposure to voices through stimulus-stimulus pairings with three children who showed low exposure to voices. The percentage of exposure was calculated from the time that each child spent listening to the audio of voices divided by the total audios presented in the session. The procedure consisted of probes to verify exposure to voices after cycles of voice-reinforcement pairing. The results showed moderate and temporary effects, suggesting that the isolated stimulus-stimulus pairing procedure is not sufficient to increase the exposure to voices in children with ABLA-R levels lower than Level 4. The need to include other procedures in with voice conditioning.